A study protocol for a randomized controlled trial of family-partnered delirium prevention, detection, and management in critically ill adults: the ACTIVATE study - Kirsten M. Fiest; Karla D. Krewulak; Bonnie G. Sept; Krista L. Spence; Judy E. Davidson; E. Wesley Ely; Andrea Soo; Henry T. Stelfox (BMC, 2020)
Abstract Background Delirium is very common in critically ill patients admitted to the intensive care unit (ICU) and results in negative long-term outcomes. Family members are also at risk of long-term complications, including depression and anxiety. Family members are frequently at the bedside and want to be engaged; they know the patient best and may notice subtle changes prior to the care team. By engaging family members in delirium care, we may be able to improve both patient and family outcomes by identifying delirium sooner and capacitating family members in care. Methods The primary aim of this study is to determine the effect of family-administered delirium prevention, detection, and management in critically ill patients on family member symptoms of depression and anxiety, compared to usual care. One-hundred and ninety-eight patient-family dyads will be recruited from four medical-surgical ICUs in Calgary, Canada. Dyads will be randomized 1:1 to the intervention or control group. The intervention consists of family-partnered delirium prevention, detection, and management, while the control group will receive usual care. Delirium, depression, and anxiety will be measured using validated tools, and participants will be followed for 1- and 3-months post-ICU discharge. All analyses will be intention-to-treat and adjusted for pre-identified covariates. Ethical approval has been granted by the University of Calgary Conjoint Health Research Ethics Board (REB19-1000) and the trial registered. The protocol adheres to the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) checklist. Discussion Critically ill patients are frequently unable to participate in their own care, and partnering with their family members is particularly important for improving experiences and outcomes of care for both patients and families. Trial registration Registered September 23, 2019 on Clinicaltrials.gov NCT04099472 .